Profeterne som litterære personae - Holt, Else K. (Dansk Teologisk Tidsskrift, 2015)
The interest within early historical-critical exegesis for the religious personality of the Old Testament Prophets has changed within parts of recent exegesis to a quest for the presentation of the prophets as literary personae. This article presents the early approach to the prophets, introduces the concept of persona from a literary and anthropological perspective as a literary strategy and a “mask” and divine mouthpiece, and connects it with the genre of ancient biography. These approaches are applied to the prophetic book of Ezekiel suggesting that this book be considered not as historiography but as a theological-literary presentation of its message through the life and acts of the literary persona of Ezekiel. The article ends with considerations of Old Testament communication of normativity through prophetic narrative.